2012
DOI: 10.1007/s00268-012-1762-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resection Rates and Survival Among Patients Aged 75 Years and Older with Esophageal Cancer: A Dutch Nationwide Population‐Based Study

Abstract: In patients of 75 years or older, surgical treatment and use of definitive CRT have increased between 1989 and 2008. Also, an increase in the use of chemotherapy as a single modality was noted. Overall 5 year survival for all cancer patients was stable but remained poor, while survival of patients who underwent esophagectomy improved significantly in the Netherlands since 1989.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 34 publications
(27 reference statements)
0
32
0
Order By: Relevance
“…This has been a topic of great debate among the clinical community, but the topic remains relatively unstudied in the head and neck region . As part of the study, a series of literature searches screened over 2,300 articles but found very few that addressed the topic of perioperative outcomes of the elderly versus younger patients . The studies uncovered focused primarily on the cervical esophagus or craniofacial resections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been a topic of great debate among the clinical community, but the topic remains relatively unstudied in the head and neck region . As part of the study, a series of literature searches screened over 2,300 articles but found very few that addressed the topic of perioperative outcomes of the elderly versus younger patients . The studies uncovered focused primarily on the cervical esophagus or craniofacial resections.…”
Section: Discussionmentioning
confidence: 99%
“…The studies uncovered focused primarily on the cervical esophagus or craniofacial resections. For example, Faiz et al and Pultrum et al conducted a review of esophagectomy patients . Each study contained over 200 patients and measured multiple complications including pneumonia, arrhythmia, respiratory distress, and wound infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common presenting symptoms are dysphagia, odynophagia, and weight loss [2,3]. It is one of the deadliest cancers worldwide with 5-year survival rates of 5.0-26.2% and the eighth most common cancer worldwide [4][5][6][7][8][9]. There are two major types of esophageal cancer: esophageal adenocarcinoma (EAC) and esophageal squamous cell cancer (ESCC) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, one or more chronic diseases such as poor organ tolerance have been reported in these populations (Faiz et al, 2012). At the same time, surgery and chemotherapy are not preferred for these patients because of the complex structure of the esophagus, lymph node metastasis, and other factors.…”
Section: Introductionmentioning
confidence: 99%